Modern knowledge based about glistening phenomenon in artificial intraocular lenses - Jurowski, Piotr; Kaczorowska-Rusin, Katarzyna; Owczarek, Grzegorz (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Glistening formations is relatively common phenomenon in acrylic IOLs that appears as a tiny clear to white sparkling areas within the material of the lens optic. While the process of glistening include not only monofocal IOLs but also multifocal IOLs and phakic IOLs and even can occur in IOLs made of other materials, problem seems to be clinically crucial. Publication comprises contemporary knowledge about glistening phenomenon.